Global Governance: Vom fordistischen Trilateralismus zum neoliberalen Konstitutionalismus - Scherrer, Christoph (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 2000)
The paper questions the emphasis proponents of global governance place on form over content as well as their narrow view of hegemony. Their theoretical approach, regime theory, originated in the policy community of internationally oriented capital groups who had gained hegemony within the USA. Regime theory was first used in support of international fordism. After this failed, these groups pushed for a neo-liberal global constitutionalism of property rights. The complex interplay between the hegemony of transnational corporations and the U.S. state becomes apparent in the struggle for a labor rights clause in the WTO.